Not all Gorgons are Greek: A red-figure kylix fragment in the collection of the Museum of Fine Arts, Budapest - Párkányi, Bence (Dissertationes Archaeologicae, 2026)
The collection of the Museum of Fine Arts, Budapest, holds an unpublished kylix fragment (Inv.no. 51.100) with an unusual depiction of the head of a Gorgon in its tondo. According to the museum’s records, the kylix was originally part of the painter Antal Haan’s collection. However, a thorough study of the published and unpublished revision records of the collection showed that the kylix cannot be identified with any of the described objects; thus, it may not have originally been part of said collection. Through careful examination of the fragment, it was possible to identify the traces of post-antique alteration on its surface, revealing that the uncommon Gorgoneion was most probably added to the original Attic black glazed vase in the 19th century. The lack of information does not allow for drawing a definitive conclusion regarding the precise place and time of alteration, but the necessary skills and the possibilities of the Békés County Museum in the decades preceding WW II, as well as the similarities with another altered piece in the collection of the Museum of Fine Arts, Budapest, suggest that the Gorgoneion was added in Italy.